Evoked pressure curves from the external anal sphincter following transcranial magnetic stimulation in healthy volunteers and patients with faecal incontinence. (December 2013) - Paris, G.; Chastan, N.; Gourcerol, G.; Verin, E.; Menard, J. F.; Michot, F.; Weber, J.; Leroi, A. M.
Abstract Aim The hypothesis was tested that evoked pressure curves (EPCs) after transcranial magnetic stimulation (TMS) would provide additional neuropathophysiological information on the descending pathways to the external anal sphincter (EAS) in patients with faecal incontinence (FI). Method Twenty‐five healthy subjects and 69 patients with FI were investigated. TMS was applied to the vertex, and EPCs were recorded with a probe placed through the EAS. TMS was performed with the EAS at rest and during contraction (facilitated responses). At least three responses were recorded for each modality. Clinical data and anorectal manometric, electrophysiological perineal and transanal ultrasound recordings were compared with respect to the EPC results. Results There was no statistically significant difference between the EPCs of healthy subjects and FI patients. Twenty‐three per cent of the FI patients had abnormal EPC latencies, with significantly lower voluntary contraction amplitudes (P = 0.03) and significantly higher rectal sensation (P = 0.04) than the other group. We found no significant difference between FI patients with and without abnormal EPC latencies in terms of clinical characteristics and electrophysiological and endoanal ultrasound parameters. There was no difference in the identified causes of the FI between the two groups. Conclusion As abnormal EPC latencies were found in 23% of FI patients with no known central neurological disease, abnormal EPC latencies might reveal undetected lesions of descending pathways in patients with FI.